The Formation of Parasocial Relationships Via Video Content in a Brand Community - Saari, Anni (2024)
Social media has made connecting with influencers easier than ever. These lower-scale celebrities are more accessible and followers can easily connect with them through their screens. Some followers create more intense connections with the influencers to the point that they form one-sided illusional relationships, known as parasocial relationships, with the influencer.